Intergenerational mobility and equality of opportunity in higher education in Cyprus - Andreou, Sofia N.; Koutsampelas, Christos (My University, 2015)
Over the last decades, public and private spending on higher education in Cyprus have increased considerably. In principle, the expansion of higher education may result to a more equitable distribution of educational opportunities. We test this idea by investigating the impact of parental educational background on the child's probability of studying in higher education using data drawn from the Cyprus Family Expenditure Surveys (1996-2009). Our results show that the parental effect has reduced over time, therefore leading to increased educational mobility. However, effective policies are needed so as to defend gains in mobility in the context of the ongoing recession and continue pursuing egalitarian educational objectives.
Keywords: Cyprus; Equality of opportunity; Higher education; Intergenerational mobility